Making the Music for ViaggIAccademici (Itinera, 2025)
How can human and artificial intelligence converge within a shared creative endeavour capable of giving musical expression to a theatrical work on artificial intelligence? This piece presents an autoethnographic account by musicologist and composer Mattia Merlini, documenting his experience in composing the stage music for ViaggIAccademici – a play addressing academic concerns regarding ChatGPT, conceived and written with the assistance of the same AI system. In seeking to translate the musical ideas emerging from an extended dialogue between ChatGPT and musicologist Maurizio Corbella, Merlini adopted the principal guidelines proposed by the AI, populating a general struc- tural framework with musical materials generated or elaborated through AI-based tools. The breadth of these suggestions resulted in the production of both MIDI files and ready- made phonograms, as well as specific AI-mediated decisions concerning timbre, struc- ture, software and arrangement, and the employment of AI-assisted mastering techniques. Throughout this process, the role of the human composer remained essential – particularly in the selection of materials, the formulation of a coherent aesthetic framework, and the adaptation of the final track to the dramaturgical demands of the play and the synchroni- sation of live performance. As an instance of practice-based research, and in continuity with the GPTheatre Project from which the play originated, this experiment offers a re- flection on the evolving relationship between human and machine creativity within a do- main traditionally regarded as distinctively and profoundly human.